2012
DOI: 10.5194/acp-12-10181-2012
|View full text |Cite
|
Sign up to set email alerts
|

In-situ measurements of atmospheric hydrofluorocarbons (HFCs) and perfluorocarbons (PFCs) at the Shangdianzi regional background station, China

Abstract: Abstract. Atmospheric hydrofluorocarbons (HFCs) and perfluorocarbons (PFCs) were measured in-situ at the Shangdianzi (SDZ) Global Atmosphere Watch (GAW) regional background station, China, from May 2010 to May 2011. The time series for five HFCs and three PFCs showed occasionally high-concentration events while background conditions occurred for 36 % (HFC-32) to 83 % (PFC-218) of all measurements. The mean mixing ratios during background conditions were 24.5 ppt (parts per trillion, 10 −12 , molar) for HFC-23,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 36 publications
1
56
1
Order By: Relevance
“…Several papers report Asian emissions of HFC-23, including those for China Stohl et al, 2010;Kim et al, 2010;Li et al, 2011;Yao et al, 2012). Recent papers by Fang et al (2014Fang et al ( , 2015 noted inconsistencies between the various bottom-up and top-down emissions estimates and provided an improved bottom-up inventory and a multi-annual top-down estimate of HFC-23 emissions for East Asia.…”
Section: Regional Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several papers report Asian emissions of HFC-23, including those for China Stohl et al, 2010;Kim et al, 2010;Li et al, 2011;Yao et al, 2012). Recent papers by Fang et al (2014Fang et al ( , 2015 noted inconsistencies between the various bottom-up and top-down emissions estimates and provided an improved bottom-up inventory and a multi-annual top-down estimate of HFC-23 emissions for East Asia.…”
Section: Regional Emissionsmentioning
confidence: 99%
“…Kim et al (2010), reported HFC-23 measurements (November 2007-December 2008 from Gosan, Jeju Island and South Korea and also estimated regional atmospheric emissions. Asian emissions of HFC-23, including those for China have been reported by Yokouchi et al (2006); Stohl et al (2010); Li et al (2011);and Yao et al (2012). Most recently, Fang et al (2014Fang et al ( , 2015 have provided bottom-up and top-down estimates of HFC-23 emissions from China and East Asia and included observed HFC-23 mixing ratios at three stations -Gosan, South Korea, and Hateruma and Cape Ochi-ishi, Japan.…”
Section: Introductionmentioning
confidence: 99%
“…5.2 and Table 3. Yao et al (2012), using the interspecies correlation method with carbon monoxide as the reference tracer, reported more recent Chinese emissions of 2 ± 1.8 Gg yr −1 in 2010-2011. This would imply some reduction in Chinese emissions compared with earlier years.…”
Section: East Asian Emissionsmentioning
confidence: 99%
“…The Medusa-GC/MS system used a similar sampling mechanism, sharing the same inlet and sampling tubing with GC-ECD system. The HFC and PFC measurements made by this system were reported by Yao et al (2012b).…”
Section: Instruments and Methodsmentioning
confidence: 99%
“…The details of the procedure were described by Yao et al (2012b). Approximately 63% of the valid results had been selected as non-background data.…”
Section: Comparison Between Performance Of Gc-ecd and Gc/ms Systemsmentioning
confidence: 99%